Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1073/pnas.90.17.8287
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in phenotypic biochemical markers in bladder epithelium during tumorigenesis.

Abstract: Phenotypic biochemical markers of oncogenesis and differentiation were mapped in bladder biopsies to investigate changes that occur in bladder tumorigenesis and to identify markers for increased bladder cancer risk. Touch preparations from biopsy specimens from 30 patients were obtained from tumors, the adjacent bladder epithelium, and random distant bladder epithelium. Markers, including DNA ploidy, epidermal growth factor receptor (EGFR), and oncoproteins, were quantified in individual cells by using quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
5

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 24 publications
(27 reference statements)
1
53
0
5
Order By: Relevance
“…EGFR expression as detected by immunohistochemistry correlates with increased grade and stage and with poor prognosis. 61 Abnormal EGFR expression is also found in cystoscopically normal-appearing urothelium in patients with TCCs elsewhere in the bladder, 62 thus supporting the notions of the existence of an urothelial field defect 63 and that abnormal EGFR expression may be an early event in BC tumorigenesis. Additionally, because ligands that work through EGFRs not only induce mitogenesis but also cellular motility, stimulation of EGFRs in malignant urothelium may encourage transepithelial motility and tumor invasion as well as proliferation.…”
Section: Egf and Egfrsmentioning
confidence: 58%
“…EGFR expression as detected by immunohistochemistry correlates with increased grade and stage and with poor prognosis. 61 Abnormal EGFR expression is also found in cystoscopically normal-appearing urothelium in patients with TCCs elsewhere in the bladder, 62 thus supporting the notions of the existence of an urothelial field defect 63 and that abnormal EGFR expression may be an early event in BC tumorigenesis. Additionally, because ligands that work through EGFRs not only induce mitogenesis but also cellular motility, stimulation of EGFRs in malignant urothelium may encourage transepithelial motility and tumor invasion as well as proliferation.…”
Section: Egf and Egfrsmentioning
confidence: 58%
“…With additional genetic or epigenetic events, it might lead to the development of cancers in the cancerization field. 19 Abnormal G-actin level is an early marker for malignant transformation in number of epithelial tumors including cancer of bladder, 10,11,14 prostate, 12 lung 20 and breast. 16 More importantly, abnormal G-actin in the adjacent, non-cancerous epithelial cells often predicts the risk of tumor development in bladder, 13 prostate 12 and breast [unpublished data].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Alternations of G-actin represent a malignancy-associated field defect that can be detected in morphologically ''normal'' epithelium adjacent to the cancer. 12,13 Abnormal G-actin level was detected in almost 50% of ''normal'' urothelium distant to areas with actual bladder cancer, 14 and, more importantly, it predicted the risk for bladder cancer recurrence after the original tumor was removed by transuretheral resection. 13 DNA5cER, the percentage of cells with a DNA content of more than 5c, is a marker of overall genetic instability.…”
mentioning
confidence: 99%
“…Immunohistochemical studies have shown no reactivity with fetal or adult normal human tissues [3,4] and variable reactivities with a few prostatic, colonic, breast and endometrial cancers [4]. Measurement of this antigen was shown to be useful for the diagnosis [5,6] and prognosis [7][8][9] of bladder cancer. Preliminary studies showed reactivity of the M series mAbs with a very-high-molecular-mass component and also with a 62 kDa component in about half of the positive samples [3].…”
Section: Introductionmentioning
confidence: 99%